Factors predictive of pelvic lymph node involvement and outcomes in melanoma patients with metastatic sentinel lymph node of the groin: A multicentre study. Issue 7 (July 2015) - Mozzillo, N.; Pasquali, S.; Santinami, M.; Testori, A.; Di Marzo, M.; Crispo, A.; Patuzzo, R.; Verrecchia, F.; Botti, G.; Montella, M.; Rossi, C.R.; Caracò, C.
Abstract Introduction The optimal extent of the groin lymph node (LN) dissection for melanoma patients with positive sentinel LN biopsy is still debated and no agreement exist on dissection of pelvic LN. This study aimed at investigating predictors of pelvic LN metastasis and prognostic significance of having metastasis in the pelvic LNs. Methods Clinicopathologic data of 740 patients with positive groin sentinel LN who underwent ilioinguinal completion LN dissection at four Italian centre were analysed. Multivariable logistic and Cox regression analysis was used to identify independent predictors of pelvic LN metastasis and to adjust prognostic significance of pelvic LN metastasis. Results More than a quarter (26%) of patients had positive non-SLNs after inguinal and pelvic lymphadenectomy, which were located in their pelvis in the 12% of cases. Older patients [(OR) 1.69; 95% confidence interval (CI) 1.02–2.78] having thick primary (OR 1.6; 95% CI, 1.01–2.53) and ≥ 2 positive SLNs (OR 2.5; 95% CI, 1.4–4.47) were more likely to harbour pelvic LN metastasis. Interestingly, 4% of all patients (34% of patients with positive pelvic LNs) had pelvic LN metastasis with negative inguinal LNs. Pelvic LN metastasis was independently associated with higher risk of recurrence and lower survival. 5-year disease free and overall survival was 30% and 50%, respectively, for patients with pelvic LN metastasis. Conclusions Pelvic LNs are frequently positive after ilioinguinal lymphadenectomy and it should be considered for all patients, especially those who are older, have thick primary and ≥ 2 positive SLN. Patients with pelvic LN metastasis have worse prognosis.